2009
DOI: 10.1007/s00705-009-0430-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biological characterization of natural variants of Citrus dwarfing viroid

Abstract: Citrus dwarfing viroid has been proposed as an agent to control tree size in high-density plantations. Thirty-three field isolates have been characterized, and the most frequent sequence/s have been identified. Five distinct variants were selected for biological characterization. Symptom expression analysis demonstrated a good correlation between leaf/stem symptoms and plant growth. The discriminating nucleotide sequence differences included two deletions and an insertion resulting in a reorganization of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
3
6
0
1
Order By: Relevance
“…consequence of a low genetic variability of this viroid species, as also observed by Owens et al (1999), Murcia et al (2009) and Eiras et al (2010). We did not observe any differences on symptoms in the plants single (Nav1) or doubly infected (Nav5 and Nav6) by HSVd and CDVd.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…consequence of a low genetic variability of this viroid species, as also observed by Owens et al (1999), Murcia et al (2009) and Eiras et al (2010). We did not observe any differences on symptoms in the plants single (Nav1) or doubly infected (Nav5 and Nav6) by HSVd and CDVd.…”
supporting
confidence: 53%
“…CEVd and HSVd are the causal agents of two wellknown citrus viroid diseases, exocortis and cachexia (or xyloporosis), respectively. Although some citrus infecting viroids, as CBLVd and CDVd, do not incite conspicuous symptoms, they can reduce tree size and crop yield (Murcia et al, 2009;Vernière et al, 2006). The control of viroids is based on prevention measures, using viroid-free bud-wood as propagation material, appropriate sanitation, treatment of cutting tools and adequate indexing procedures (Duran-Vila & Semancik, 2003;Eiras et al, 2009).…”
mentioning
confidence: 99%
“…Swingle) (CTV bioindicator). Citrus dwarfing viroid (CDVd) (GenBank accession number EU934004), inducing moderate but specific symptoms in etrog citron (4), and CTV (T-305 strain), inducing symptoms in Mexican lime (5), were chosen for this study. To synchronize infection, Volkamer lemon (Citrus volkameriana Ten.…”
mentioning
confidence: 99%
“…The results reported here on the modulation of symptom expression in CEVd‐infected Etrog citron plants show the same trend as those described for PSTVd. It was also observed that CEVd COL ‐infected plants displayed extremely subtle leaf distortion, suggesting that other positions of the viroid molecule may also play a role in the modulation of symptom expression, as already reported for the T L , T R and C domains of PSTVd (Qi and Ding, 2003; Sano et al ., 1992) and for the T L domain of Citrus viroid V (CVd‐V) and Citrus dwarfing viroid (CDVd), two members of the genus Apscaviroid (Murcia et al ., 2009a; Serra et al ., 2009).…”
mentioning
confidence: 99%